Fatigue design of cast steel nodes in tubular bridge structures - Haldimann-Sturm, S. C. (2008)
Due to their aesthetic and structural advantages, tubular space truss structures are enjoying increasing popularity in modern bridge construction. The use of cast steel nodes for the joints between the circular hollow section members is also becoming increasingly popular. The fatigue design of such joints, however, requires additional knowledge with respect to their fatigue resistance. Previous experimental investigations showed very clearly that the fatigue behaviour is governed by the welds between the casting stubs and the hollow section members. This paper presents a methodology for the determination of allowable initial sizes of casting defects as a function of the required fatigue resistance of the welds. The relative influence of the main parameters is quantitatively discussed and recommendations for design are given.